2022
DOI: 10.1021/acs.iecr.2c00181
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Structural Collapse and Thermal Runaway to Improve the Electrochemical Performance and Safety of LiNi0.8Co0.1Mn0.1O2 by a Negative-Thermal-Expansion Material of Al2(WO3)4

Abstract: Nickel-rich layered oxides such as LiNi0.8Co0.1Mn0.1O2 (NCM811) deliver high specific capacity and attract extensive interest for applications, but they still face some challenges of capacity fade and thermal runaway. Herein, NCM811 was modified with a cheap orthorhombic negative-thermal-expansion (NTE) material of Al2(WO3)4 to improve its electrochemical performance and safety by adjusting the heat, deformation, and interface via a simple strategy. The NCM811 material modified with 7 wt % Al2(WO3)4 (NA7) exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…177 The addition of a negative-thermal-expansion (NTE) material of Al 2 (WO 3 ) 4 leads to improvement in the thermal stability. 178 The formation of the rock-salt layer on the surface of NCM811 is reported to enhance the thermal stability of an NCM cathode with high Ni contents. 179 The change in the total heat generation with degradation suggests a strong correlation between the heat generation and crystal structure changes during cycling, as indicated by differential scanning calorimetry (DSC) measurements and XAS measurements.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…177 The addition of a negative-thermal-expansion (NTE) material of Al 2 (WO 3 ) 4 leads to improvement in the thermal stability. 178 The formation of the rock-salt layer on the surface of NCM811 is reported to enhance the thermal stability of an NCM cathode with high Ni contents. 179 The change in the total heat generation with degradation suggests a strong correlation between the heat generation and crystal structure changes during cycling, as indicated by differential scanning calorimetry (DSC) measurements and XAS measurements.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The surface coating of high-nickel cathode materials mainly includes metal oxides, metal fluorides, metal phosphates, lithium-containing compounds, and non-metallic compounds. Metal oxide surface coatings mainly include SiO 2 [158][159][160], ZrO 2 [161], TiO 2 [162][163][164], Al 2 O 3 [165], Ta 2 O 5 [166], Al+Ti [167], Al+W [168], Co+Ti [169], Co+B [170], Co+Al [171], La+Ca [172], etc. Sun et al [163] prepared spherical high-nickel cathode material LiNi 0.9 Co 0.08 Al 0.02 O 2 with 0.4 wt% TiO 2 coating using the immersion-hydrolysis method.…”
Section: Interfacial Modification By Surface Coatingmentioning
confidence: 99%
“…Structural analysis showed that NCA-Ta 2 O 5 maintained a good spherical structure without obvious cracks after 200 cycles at 1 C, while the original NCA experienced severe structural collapse. Wang and colleagues [167] synthesized NCM811 with Al and W coatings. The coated NCM811 exhibited excellent electrochemical stability and safety, and the capacity retention rates after 100 cycles at 25 • C and 60 • C were improved by 13.8% and 25.4%, respectively.…”
Section: Interfacial Modification By Surface Coatingmentioning
confidence: 99%
“…From the local amplification of the (003) diffraction peak, compared to the original sample, the (003) peak of the SC-NCM622-1.0% WO 3 sample shifted significantly towards a lower angle, indicating an increase in the c-axis of the sample. The increased interlayer spacing was significantly beneficial for lithium electron transport during the charging and discharging of the lithium battery [30]. The lattice parameters of the ratio of all samples I (003)/I (104) are shown in Table 3.…”
Section: Morphology and Structural Analysismentioning
confidence: 99%